bHLH-O proteins balance the self-renewal and differentiation of Drosophila neural stem cells by regulating Earmuff expression - Li, Xiaosu (Dev Biol, 2017)
Balancing self-renewal and differentiation of stem cells requires differential expression of self-renewing factors in two daughter cells generated from the asymmetric division of the stem cells. In Drosophila type II neural stem cell (or neuroblast, NB) lineages, the expression of the basic helix-loop-helix-Orange (bHLH-O) family proteins, including Deadpan (Dpn) and E(spl) proteins, is required for maintaining the self-renewal and identity of type II NBs, whereas the absence of these self-renewing factors is essential for the differentiation of intermediate neural progenitors (INPs) generated from type II NBs. Here, we demonstrate that Dpn maintains type II NBs by suppressing the expression of Earmuff (Erm). We provide evidence that Dpn and E(spl) proteins suppress Erm by directly binding to C-sites and N-boxes in the cis-regulatory region of erm. Conversely, the absence of bHLH-O proteins in INPs allows activation of erm and Erm-mediated maturation of INPs. Our results further suggest that Pointed P1 (PntP1) mediates the dedifferentiation of INPs resulting from the loss of Erm or overexpression of Dpn or E(spl) proteins. Taken together, these findings reveal mechanisms underlying the regulation of the maintenance of type II NBs and differentiation of INPs through the differential expression of bHLH-O family proteins.